Evaluation of biocontrol agents and mycorrhizae against Gloeocercospora sorghi causing zonate leaf spot of sorghum (Sorghum bicolor) with respect to disease reduction and growth parameters - YOGENDRA SINGH, GAURAV VERMA* (Indian Phytopathology, 2015)
The experiment was conducted to develop effective biocontrol system for management of zonate leaf spot of sorghum [Sorghum bicolor (L.) Moench] caused by Gloeocercospora sorghi, at G.B. Pant University of Agriculture and Technology, Pantnagar, during 2013. Five isolates of Trichoderma harzianum Th, two isolates of Pseudomonas fluorescens Pf and one isolate of Glomus intraradices were evaluated for growth promotion, disease reduction, chlorophyll content and green fodder yield in sorghum against G. sorghi under field conditions. Biocontrol agent (Th-32) was found best in increasing root length (26.89cm) and stem diameter (1.35cm) in PC-4, while it was 27.12cm (root length) and 1.41cm (stem diameter) in PC-5. However, significant increase in shoot length (172.12cm and 185.89cm) was recorded in Pf-31 in PC-4 and PC-5, respectively at 45 days after sowing (DAS). Among all isolates, Th-32 resulted in maximum reduction of disease severity in both PC-4 (28.74%) and PC-5 (33.81%). Maximum chlorophyll content was observed in Th-32 treated PC-4 plants (2.356 mg/g fr.wt.) while in PC-5, it was maximum in Th-31 treated plants (2.976 mg/g fr.wt.). Green fodder yield was observed to be maximum in Th-32 treated plots of both PC-4 (27.15kg/plot) and PC-5 (38.19 kg/plot) cultivars. Thus, present study demonstrates the possible role of Th-31, Th-32 and Pf-31isolates in growth promotion, disease reduction, chlorophyll content and green fodder yield of sorghum.